Electrochemical properties of octakis(hydroxyethylthio)-substituted phthalocyanines - (:unkn) unknown (JOHN WILEY & SONS LTD, 2000)
Cyclic voltammetry of octakis(hydroxyethylthio)-substituted phthalocyanines with 2H (H2OHETPc), Zn(II) ((ZnOHETPc)-O-II(-2)) and Co(II) (Co-II(OHETPc(-2)) in the phthalocyanine core has been investigated in dimethylsulfoxide (DMSO), and some of the results were evaluated together with their absorption spectra in the visible range. The redox processes due to both aggregated and non-aggregated species were observed on the voltammograms of phthalocyanines with Zn(II). The effect of chloride ion on the cyclic voltammetry of (CoOHETPc)-O-II(-2) has been investigated in the DMSO/ClO4- couple. The comparison of cyclic voltammetry for (CoOHETPc)-O-II in the absence and presence of chloride ion showed that chloride ion does not bind to either Co(II) or Co(I) but does bind very strongly to Co(III). The detailed electrochemistry of (CoOHETPc)-O-II(-2) was investigated in terms of the Co(I)/Co(II) and Co(II)/Co(III) redox couples, and various equilibria related to the species coordinated to Co(II) and Co(III) in the phthalocyanine core. Copyright (C) 2000 John Wiley & Sons, Ltd.
Keywords: phthalocyanines; thiaethers; pentanuclear complex; cyclic voltammetry; COBALT PHTHALOCYANINES; METAL PHTHALOCYANINES; ELECTRODE-POTENTIALS; OXIDATION; COMPLEXES; SPECTROELECTROCHEMISTRY; ZINC; METALLOPHTHALOCYANINES; REDUCTION; SOLVENTS